Hair like Obama's, hands like Lebron's - Weatherford, Carole Boston, 1956- (Abrams Appleseed, 2024)
"From Colin Kaepernick to Martin Luther King, Jr. to Benjamin Crump, Hair Like Obama's, Hands Like Lebron's is a picture book celebration of Black history and excellence from New York Times bestselling and award-winning author Carole Boston Weatherford, illustrated by Savanna Durr." --